2016
DOI: 10.1002/2016sw001376
|View full text |Cite
|
Sign up to set email alerts
|

The latitudinal variation of geoelectromagnetic disturbances during large (Dst≤−100 nT) geomagnetic storms

Abstract: Geoelectromagnetic disturbances (GMDs) are an important consequence of space weather that can directly impact many types of terrestrial infrastructure. In this paper, we analyze 30 years of SuperMAG magnetometer data from the range of magnetic latitudes 20°≤λ≤75° to derive characteristic latitudinal profiles for median GMD amplitudes. Based on this data, we obtain a parameterization of these latitudinal profiles of different types of GMDs, providing an analytical fit with Dst‐dependent parameters. We also obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 53 publications
6
47
0
Order By: Relevance
“…Quantitatively, Beamish et al [] found that the contrast in resistivity at the coastal boarders produced electric field enhancements as high as 4 V km −1 for an auxiliary magnetic field ( H = 1 A m −1 or B ≈1256 nT) and a period of 10 min, a perturbation that approaches the electric field fluctuations measured by Thomson et al [] during the Halloween storm in 2003. This is consistent with 100 year values at HAD reported by Thomson et al [] and estimates for similar latitudes in Woodroffe et al [].…”
Section: Conductivity Modelssupporting
confidence: 93%
“…Quantitatively, Beamish et al [] found that the contrast in resistivity at the coastal boarders produced electric field enhancements as high as 4 V km −1 for an auxiliary magnetic field ( H = 1 A m −1 or B ≈1256 nT) and a period of 10 min, a perturbation that approaches the electric field fluctuations measured by Thomson et al [] during the Halloween storm in 2003. This is consistent with 100 year values at HAD reported by Thomson et al [] and estimates for similar latitudes in Woodroffe et al [].…”
Section: Conductivity Modelssupporting
confidence: 93%
“…These products are listed below, along with references to existing or developing examples of their generation: New mapping products Global maps of magnetospheric mass density as a function of L and local time including location and characterization of the plasmapause, based on field line resonance‐based remote sensing (e.g., Chi et al, ; Menk & Waters, ). Global and/?or regional maps of equatorial electrojets (Yizengaw et al, , ) and auroral zone equivalent currents (Weygand et al, ). Routine production of maps of global equivalent current data from magnetometers and other instruments such as the SuperDARN radars. Derivation of the full vector electric current system in the ionosphere requires simultaneous magnetic field data from space and the ground (Lotko, ). Maps of magnetic perturbations and the synoptic open/?closed boundary of the magnetosphere in both polar caps (Urban et al, ). Statistical maps of magnetic perturbations (Pothier et al, ; Weimer et al, ) and various categories of ULF waves as functions of solar wind/?IMF drivers and/?or geomagnetic activity. Quick‐look event‐specific maps and/?or magnetic keograms of Pc5 ULF waves (Kozyreva et al, ) and other ULF wave categories superposed on magnetospheric regions such as the polar cap, auroral zone, plasmatrough, and plasmasphere. Global and regional maps and parameterizations of geomagnetic disturbances (and time derivatives) that drive ground‐induced currents (e.g., Carter et al, ; Love et al, ; Woodroffe et al, ). Interhemispheric comparisons of regional ULF wave activity (e.g., Kim et al, , ; Zesta et al, ), electrojet currents, and cusp and substorm phenomena, in order to understand the way energy from the solar wind is transmitted asymmetrically to Earth's high‐latitude regions. New activity indices, indicators, and tools Regional activity indices ( K indices) specifying localized activity. Stacked plots of time series of “virtual magnetometers” at fixed local times. Visual products using the ULF index (Kozyreva et al, ; Pilipenko et al, ). Development of more “interpretive” capabilities such as automated identification and location of substorms (Murphy et al, ) and Pi2 pulsations. Shared software tools for analysis of magnetometer data, as is done, for example, in the seismic and astrophysical communities. …”
Section: Higher‐level Data Productsmentioning
confidence: 99%
“…Global and regional maps and parameterizations of geomagnetic disturbances (and time derivatives) that drive ground‐induced currents (e.g., Carter et al, ; Love et al, ; Woodroffe et al, ).…”
Section: Higher‐level Data Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…And, indeed, it is certainly true that each storm has its own unique time‐dependency. Recognizing this, one way to characterize geomagnetic activity is in terms of extreme‐event variation recorded at ground observatories—this activity can be roughly described in terms of a latitude‐dependent function [e.g., Ngwira et al , ; Love et al , ; Woodroffe et al , ]. The highest levels of geomagnetic activity tend to be concentrated underneath the auroral oval and within about 55 to 65° geomagnetic latitude.…”
Section: Geoelectric Hazard Mapsmentioning
confidence: 99%